2006
DOI: 10.3727/000000006783980900
|View full text |Cite
|
Sign up to set email alerts
|

IL-2, TNF-α, and Leptin: Local Versus Systemic Concentrations in NSCLC Patients

Abstract: One recent line of cancer research shows increasing interest for biological factor such as IL-2, TNF-alpha, and leptin, which have been found to participate in the development and progression of non-small cell lung cancer (NSCLC). The aim of this study was to measure IL-2, TNF-alpha, and leptin concentrations in the airways and in the systemic circle of patients with NSCLC, investigating the role of these factors in the lung tumors. We enrolled 32 patients (17 men, 71 +/- 7 years) with a histological diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 2 publications
5
57
0
4
Order By: Relevance
“…In a previous study from our group (25), protein carbonylation levels, as measured by malondialdehyde (MDA)-protein adducts, were also increased in the normal epithelium of patients with LC, especially in patients with underlying COPD, whose levels were significantly greater than in those without this disease. These findings were consistent with those reported in previous investigations, in which a rise in different redox markers was demonstrated in lung tissues or blood of patients with LC (19,20,25,37,101).…”
Section: Redox Balancesupporting
confidence: 83%
See 1 more Smart Citation
“…In a previous study from our group (25), protein carbonylation levels, as measured by malondialdehyde (MDA)-protein adducts, were also increased in the normal epithelium of patients with LC, especially in patients with underlying COPD, whose levels were significantly greater than in those without this disease. These findings were consistent with those reported in previous investigations, in which a rise in different redox markers was demonstrated in lung tissues or blood of patients with LC (19,20,25,37,101).…”
Section: Redox Balancesupporting
confidence: 83%
“…Other cytokines and growth factors such as tumor necrosis factor (TNF)-alpha, vascular endothelial growth factor (VEGF), and transforming growth factor (TGF)-beta have also been shown to participate in the development of LC in patients with underlying respiratory conditions (30,101). Identification of additional inflammatory molecules that may be involved in the development of LC among patients with COPD and/or tumor progression is of relevance as they offer potential for the design of novel therapeutic strategies in the treatment of LC (100,102).…”
Section: Chronic Inflammationmentioning
confidence: 99%
“…Biomarkers are originated from lower airways, but there is the possibility of saliva, upper respiratory tract contamination. To date, changes of biochemical markers of inflammation and oxidative stress have been most extensively investigated in patients with asthma (38,39), COPD (40,41), cystic fibrosis (42,43), and lung carcinoma (44) and less extensively in other pulmonary diseases (45). There is a general opinion that profiles of different analytes in EBC could be chosen in the future to help in the differential diagnosis of pulmonary diseases (16).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated that interleukin2, TNF alpha, leptin, and endothelin-1 are present in higher levels in the EBC from LC patient compared to normal controls. These levels also appeared to correlate with the stage of the disease [67][68][69]. Like VOCs, EBC still requires further validation and large scale trials.…”
Section: Exhaled Breath Condensate (Ebc)mentioning
confidence: 95%